2009
DOI: 10.1080/19388160802711386
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Demand Modeling and Forecasting: A Review of Literature Related to Greater China

Abstract: Greater China, including Mainland China, Hong Kong, Macau and Taiwan, contributes significantly to both regional and global tourism developments. Empirical research on tourism demand modelling and forecasting has attracted increasing attention of scholars both within and beyond this region. One hundred and eighty articles are identified that were published in both English and Chinese language journals since the beginning of the 1990s. This study presents the largest scale of literature survey on tourism demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…This is consistent with most findings in the general literature on tourism demand (Li, 2009). Taking overseas holidays is still a relatively recent phenomenon and is limited to urban populations, especially to the three most economically developed regions of Beijing, Shanghai, and Guangdong Province.…”
Section: Demand Elasticitiessupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with most findings in the general literature on tourism demand (Li, 2009). Taking overseas holidays is still a relatively recent phenomenon and is limited to urban populations, especially to the three most economically developed regions of Beijing, Shanghai, and Guangdong Province.…”
Section: Demand Elasticitiessupporting
confidence: 90%
“…Li (2009) reviewed 200 studies including 137 articles published in Chinese and concluded that the outbound demand analysis related to the Greater China region (including mainland China, Hong Kong, Macau, and Taiwan) is a new research direction for researchers. This study, therefore, fills this research gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding is consistent with previous studies in the tourism demand literature, in which international tourism demand for Greater China is generally found to be a luxury product (Li 2009). However, the income elasticity of tourism demand in Mainland China among Hong Kong tourists is smaller than the average income elasticity (around 2) of tourism demand in Mainland China among other source markets reported in Li (2009). Although the coefficient is not statistically significant, the relative price negatively affects tourist arrivals (coefficient = −0.1865).…”
Section: Resultssupporting
confidence: 93%
“…The geographic conditions of these regions have a particularly strong influence on their climate patterns and natural attributes. As a result, China’s tourism industry, including Hong Kong, exhibits strong seasonality within its regions (Li 2009). Figure 1 shows the seasonal variations in demand for Mainland tourism among Hong Kong residents.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate tourism forecasts are key inputs for effective government policy planning to enable tourism development and economic growth (Jiao & Chen, 2019;Li, 2009). Number of tourist arrivals are the most commonly used indicator to measure overall changes in tourism demand (Wu et al, 2017).…”
mentioning
confidence: 99%